Evaluation of the shoe-surface interaction using an agility maneuver - Pedroza, A.; Fernandez, S.; Heidt, R.; Kaeding, C. (Medicine & Science in Sports & Exercise, 2010)
Purpose: An increase in traction between the shoe and a playing surface can result in increased forces to be absorbed by the structures of the lower extremity. Alternately, decreased traction causes impaired performance. We hypothesized that changes in the coefficient of friction (CoF) will affect subjective and objective measures of performance for an agility maneuver.